2024
DOI: 10.1039/d3nj04206e
|View full text |Cite
|
Sign up to set email alerts
|

The thermal response of lead sensitized terbium emission in group II sulfide nanoparticles: importance of spatial proximity and band gap engineering

Madhumita Bhar,
Nayan Bhunia,
Prasun Mukherjee

Abstract: Lead sensitized terbium emission in zinc sulfide nanoparticles is thermally irreversible, in which the spatial proximity of lead–terbium is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The Tb−Pb spatial proximity and codopant electronic energy level alignments have been identified as important control parameters that guide the Tb 3+ emission brightening. 30 The results from the postsynthetically modified NPs suggest that synthetically codoped Zn(TbPb)S NPs should also exhibit this sensitization effect. A synthetic condition-dependent display of emission properties in doped semiconductor NPs finds notable literature precedence.…”
Section: ■ Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The Tb−Pb spatial proximity and codopant electronic energy level alignments have been identified as important control parameters that guide the Tb 3+ emission brightening. 30 The results from the postsynthetically modified NPs suggest that synthetically codoped Zn(TbPb)S NPs should also exhibit this sensitization effect. A synthetic condition-dependent display of emission properties in doped semiconductor NPs finds notable literature precedence.…”
Section: ■ Introductionmentioning
confidence: 97%
“…The broadening of the profile is a reflection of the smaller NP dimensionality (vide supra) and is consistent with our previous observations. 27,30 Formation of Zn(TbPb)S NPs with varying nominal amounts of Pb 2+ retains the characteristic bands of ZnS and does not have any dramatic effect to generate any additional phase that can be correlated to the formation of Pb-related phases. Thus, it can be unequivocally concluded that both Tb 3+ and Pb 2+ act as dopants in the ZnS matrix.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation